2018
DOI: 10.1155/2018/8498651
|View full text |Cite
|
Sign up to set email alerts
|

Possible Modulation of Vascular Function Measures in Rheumatoid Arthritis by Homocysteine

Abstract: The effect of homocysteine on cardiovascular diseases is still equivocal, especially in rheumatoid arthritis patients. In this investigation, the association between homocysteine with blood flow and vascular resistance in rheumatoid arthritis was examined. Serum levels of homocysteine were determined in thirty-one rheumatoid arthritis patients and nineteen apparently healthy subjects using ELISA. Additionally, strain-gauge plethysmography was used to determine both forearm blood flow and vascular function at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In general, HCYS levels above 1.4 mg/L are considered elevated, and CV risk has been shown to increase in a linear fashion for HCYS levels greater than this threshold. 6,40,41 Because patients in both tertile 2 (HCYS reduction of 1.3 mg/L) and tertile 3 (HCYS reduction of 1.1 mg/L) had achieved HCYS reductions of less than 1.4 mg/L, CV risk estimates for these serum tertiles were not statistically significantly different. The lack of doseresponse association for serum folate and CV mortality is consistent with findings in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In general, HCYS levels above 1.4 mg/L are considered elevated, and CV risk has been shown to increase in a linear fashion for HCYS levels greater than this threshold. 6,40,41 Because patients in both tertile 2 (HCYS reduction of 1.3 mg/L) and tertile 3 (HCYS reduction of 1.1 mg/L) had achieved HCYS reductions of less than 1.4 mg/L, CV risk estimates for these serum tertiles were not statistically significantly different. The lack of doseresponse association for serum folate and CV mortality is consistent with findings in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…There is a higher prevalence of several traditional risk factors among the RA population. Higher systolic and diastolic blood pressures (SBP/DBP) are seen in RA [3][4][5][6]10,17]. In several studies, higher SBP was associated with higher arterial stiffness [6,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine is considered a biomarker of vascular function, but causality is not yet proven. Homocysteine amount is generally higher in RA patients, but some studies showed not constant increase in the homocysteine level among RA patients mostly because of B6 supplements [10]. Adequate intake of B vitamins might prevent homocysteine elevation in RA patients.…”
Section: Homocysteinementioning
confidence: 95%
See 2 more Smart Citations